Arsenic Content in Groundwater in Two Regions of the Republic of North Macedonia: The Hidden Public Health Threat - Dimovska, Mirjana; Minov, Atanas (Open Access Macedonian Journal of Medical Sciences, 2025)
BACKGROUND: Arsenic groundwater contamination is a challenging public health threat in many regions globally, it also poses a threat to sustainable agriculture and food production. Hyperpigmentation, hyperkeratosis and skin lesions on the palms and feet are the first symptoms of the long term exposure, both, trough drinking water and food. In terms of its carcinogenic effect, long term exposure to Arsenic is associated with cancer of the bladder, lungs, skin, kidneys, nasal passages, liver and prostate. AIM: The aim of the study was to analyze the effects of long-term exposure to low levels of arsenic in groundwater in two regions in the Republic of North Macedonia - Kumanovo municipality (Northeast Region) and Gevgelija municipality (Southeast Region), related to the cancer incidence rate and some other related diagnoses. METHODS: The relationship between arsenic concentration in groundwater and the death rate due to various causes of deaths was investigated using Poisson Regression. RESULTS: Our study despite the methodological limitations suggested important links between the chronic exposure to Arsenic in groundwater and adverse health outcomes such as diabetes mellitus, cancer of larynx, liver, bronchus and lung cancer, stomach cancer leukaemia, lymphoma and cancer of prostate, from total malignancies and malignancies of digestive organs. CONCLUSIONS: The policy and actions in the RN Macedonia supposed to be focus on awareness raising of the local population about the adverse effects of groundwater used for irrigation, crop cultivation or even drinking, replacing high content arsenic sources (wells) with some more safe alternatives, regular monitoring of the arsenic content in the groundwater, drinking water and food (crops) or eventually, ban of the use of arsenic-contaminated wells as a last resort.